Application of multi-verse optimiser-based fuzzy-PID controller to improve power system frequency regulation in presence of HVDC link. (2018) - Kouba, Nour E.L. Yakine; Menaa, Mohamed; Hasni, Mourad; Boudour, Mohamed
This paper presents the design of a novel optimal fuzzy-PID controller-based multi-verse optimiser (MVO) for load frequency control (LFC) of a two-area power system interconnected via high voltage direct current (HVDC) transmission link. The MVO algorithm was adopted to estimate the unknown parameters of the test system and model the HVDC link for the LFC analysis, and then, was used to optimise the fuzzy-PID controller parameters including the scaling factors of fuzzy logic and the PID controller gains. To demonstrate the effectiveness of the proposed control strategy, a two-area power system with HVDC link connection was investigated for the simulation. A comparative study of performance of proposed controller, fuzzy logic and conventional PID controller was performed. The obtained results satisfy the LFC requirements and reveal that the optimised fuzzy-PID controller-based MVO algorithm enhances power system frequency regulation in presence of HVDC link.